Learning PowerShell - Hassell, Jonathan (De|G Press, 2017)
Learning PowerShell is a custom-built, handcrafted, painstakingly curated book designed to get you from total PowerShell newbie to confident PowerShell user in as little as four weeks. This book assumes no prior knowledge, perfect for non-developers and GUI addicts who recognize that PowerShell is the future but need a good bit of handholding to achieve mastery. It is also a simple guide for the hundreds of thousands of PowerShell users who have not attained the level of PowerShell knowledge that they really need. With Learning PowerShell at your side, you will see that you don't have to be a developer to use PowerShell and you don't need to be a scripting wizard to derive value from integrating PowerShell into your daily administrative activities. The book is a learning resource that covers every topic worth discussing for a PowerShell beginner, with a depth of explanation unparalleled by any book currently on the market. With this book, you don't have to have a lot of time to learn the language and you can begin applying what you master almost immediately. Even skeptics of PowerShell, and command lines in general, will come away with a renewed sense of respect for the language and ideas on how to put it to use.